IDENTIFIKASI 16S RRNA DAN UJI ZIMOGRAFI BAKTERI ASAL PANTAI PAPUMA PENGHASIL ENZIM FIBRINOLITIK SEBAGAI ANTI ATHEROTHROMBOSIS - A.S, Pananjung; I, Novanda asri; Nuryady, M Mirza; Ulfa, Evi Umayah (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Atherotrombosis is a disease caused by a blood clot (thrombus) in a blood vessel, and it can be the leading cause of death in the world. Atherotrombosis disease can be overcome with thrombolytic agents, one of which is a fibrinolytic enzyme but it has a expensive price, so we needto looking for a new fibrinolytic agent in this case the bacteria, from Papuma coastal. This research is a follow-up from past research, to identify the bacteria from papuma by using 16S rRNA, and to know the Enzyme activated by using Zymografi.The result of this research is, the bacteria identification by 16S rRNA is similar with Microbacterium testaceum with similarity percentage is about 97%. This bacteria is positive fibrinolityc bacteria it can showed by the result of Zymografi test, there is a one white band on zymografi gel, and because the protein marker on zymografi gel is unseen, so we just used theÂ qualitative observation. Keywords:Atherotrombosis, fibrinolitic, 16s rRNA, BacteriaÂ Identification, Zimografi.Â